Innovative fire protection systems - Marek Horvát (Košická bezpečnostná revue, 2019)
Fire is a complex of physicochemical phenomena based on combustion, heat transfer and gas exchange processes; it is the uncontrolled combustion of substances and materials that cause damage. According to the temperature-time characteristic we divide the fire phases into 4 phases. The first phase of flame-free decomposition is the time from fire to intense combustion (ignition) according to the type of material. The second phase of the developing fire is the time from the intensive development of the fire (ignition) until to get hold fire of all combustible materials. The third phase of the developed fire is the time from the volumetric flare-up until the time when the burning intensity begins to decrease and the fourth is the phase of the fire demise, ie the time from the reduction of the intense burning until the complete burning of the combustible material. Methods of interrupting combustion are the chemical and physical processes of gradual and purposeful action that cause combustion to cease. Fire extinguishing is a measure that interrupts the combustion process. It is recommended to extinguish with fog devices which are divided into low pressure systems and high pressure systems.